(untitled) (European Journal of Pure and Applied Mathematics, 2012)
We obtain the asymptotic expansion of the Fourier integrals \[_0^∞ t^ u-1 -.8ex extstyle (xt) (-t^n/n) dt\] for large complex values of x and integer n>2 by means of the asymptotic theory of the Wright function. Asymptotic approximations for both the real and complex zeros of these integrals are considered. These results are extended to p-dimensional Fourier integrals of a similar structure.